2021
DOI: 10.1002/adma.202170384
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Photoclick (Bio)Resins for Fast Volumetric Bioprinting (Adv. Mater. 49/2021)

Abstract: Volumetric Bioprinting Volumetric bioprinting: the next move. In article number 2102900, Marcy Zenobi‐Wong and co‐workers further develop a revolutionary type of light‐based 3D printing called “volumetric” or “tomographic” printing by introducing the use of an optimized, high‐performance photo click‐based photoresin that results in extremely fast and biocompatible printing of complex 3D models. Illustration by Riccardo and Massimiliano Rizzo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…This specific size was selected to generate filaments that could completely embed the produced organoids, even though finer printing resolution are possible as shown before in Figure 1B,C, in which resolution superior to what is shown with volumetric printing up to date has been demonstrated. [ 15,16,24,25 ] In an ideal print, both the thick border of the disc and the thinner filament, herein used as a benchmark to quantify the printing resolution, should solidify at the same time after receiving the same, optimal light dose. Exceeding this optimal dose will cause overcuring of the fine feature, thickening of the filament wall, and eventually clogging of the disc.…”
Section: Resultsmentioning
confidence: 99%
“…This specific size was selected to generate filaments that could completely embed the produced organoids, even though finer printing resolution are possible as shown before in Figure 1B,C, in which resolution superior to what is shown with volumetric printing up to date has been demonstrated. [ 15,16,24,25 ] In an ideal print, both the thick border of the disc and the thinner filament, herein used as a benchmark to quantify the printing resolution, should solidify at the same time after receiving the same, optimal light dose. Exceeding this optimal dose will cause overcuring of the fine feature, thickening of the filament wall, and eventually clogging of the disc.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have demonstrated the fabrication of similar structures under concentrations of only 10 000 or 1 million cells mL −1 . [ 8,13 ] At a concentration of 4 million cells mL −1 , the scattering mean free path of the resin is l s = 3.6 mm. The cell‐laden constructs were printed in vials whose inner diameter is L = 13 mm.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, a recent publication by Rizzo et al. [ 200 ] showed that when gelatin–norbornene (GelNB) was used for volumetric tomographic printing, there was no need for postprinting crosslinking. Although both GelMA and GelNB uses gelatin as the parent polymer, the crosslinking process is fundamentally different (chain‐growth vs step‐growth polymerization), which might explain the difference in bioresin performance observed.…”
Section: Bioresins and Recent Advancesmentioning
confidence: 99%